Assessment of two sludge stabilization methods in a wastewater treatment plant in Sotaquirá, Colombia - José Castellanos-Rozo, Jaqueline A. Galvis-López, Nuri A. Merchán-Castellanos, Elsa H. Manjarres-Hernández, Alex L. Rojas (Universitas Scientiarum)
Wastewater sludge is a by-product of wastewater treatment; it is often employed in agricultural processes following appropriate microbiological stabilization. In this study, we evaluated two methods of sludge stabilization in the wastewater treatment plant of Sotaquirá, Colombia. The two assessed stabilization methods were dewatering on drying beds and alkaline stabilization. The stabilization through dewatering on drying bed was carried out for five months. Alkaline stabilization was conducted for 96 hours with three concentrations of calcium oxide, 7 %, 9 %, and 13 % w/w. Humidity, pH, organic carbon, phosphorus, organic nitrogen, fecal coliforms, somatic phages, total helminth eggs, and Salmonella sp. were monitored monthly for the sludge under dewatering treatment and at 0, 12, 24 hours for sludge under alkaline stabilization treatment. Both treatments succeded in eliminating Salmonella sp. Helminth eggs were eliminated by alkaline stabilization, whereas it was reduced to one or zero helminth eggs with the dewatering treatment. Somatic phages were eliminated with alkaline stabilization but were only reduced to 3.52 log CFU/g with the dewatering method. Dewatering on drying beds produced biosolids that can be used for soil restoration. Whereas alkaline stabilization produced biosolids that can be used for agricultural purposes. Alkaline stabilization with 9 % and 13 % calcium oxide ostensibly reduced nitrogen and phosphorus contents in the sludge, whereas 7 % calcium affected less the phosphorus concentration of the sludge. These results indicate that sludge dewatering on drying beds is an effective sludge sanitation protocol to be in implemented in small wastewater treatment plants, such that in Sotaquirá, Colombia.